Antibacterial, antibiofilm activities and toxicity of uvaria chamae P. beauv (annonaceae) (2024)
"Background: Bacteria biofilms are a serious global health concern. The rapid increase of antimicrobial resistance in diarrheagenic bacteria due to biofilm formation has limited the clinical usefulness of some antibiotics in circulation. Objectives: Uvaria chamae has shown broad spectrum antibacterial activity, hence the need to study its antibiofilm activity against enteroaggregative Escherichia coli (EAEC) strains implicated in paediatric diarrhoea. Methods: Samples of authenticated U. chamae root, stem and leaf were collected, air-dried, ground and extracted by cold maceration in dichloromethane and methanol separately. The EAEC strains tested were; O42, DH5α, MN5DE, D25D and D28I. The plant extracts were subjected to quantitative and qualitative phytochemical screening and the 50% lethality (LC50) brine shrimp assay carried out. Extracts were screened for antibacterial activity using agar diffusion method, while agar dilution and broth dilution methods were used to determine minimum inhibitory and bactericidal concentrations, respectively. Biofilm inhibition of the active extracts was investigated by crystal violet method. Results: All the EAEC strains were multi-drug resistant, but susceptible to gentamicin and azithromycin. Dichloromethane leaf extract (DLE) and methanol leaf extract (MLE) inhibited the growth of the tested EAEC strains with the MIC of MLE D28I being MIC 3.75 mg/mL. The percentage biofilm inhibition by MLE against EAEC strains O42, MND5E and D25D were 72%, 74.5%, and 63%, respectively. Alkaloids were the most abundant in the methanol leaf extract of U. chamae (MLE). The extracts had LC50 >1000 μg/mL. Conclusion: Uvaria chamae is non-toxic and possesses antibiofilm potential that could be further developed as a natural remedy for diarrhoea.